Hubungan Faktor yang memengaruhi Tingkat Literasi Pengobatan Masyarakat Kota Semarang dengan pendekatan Teori Health Belief Model - Indriyati Hadi Sulistyaningrum; Fatihah Bintang Indriasari; Erki Arfianto; Adinda Savariani; Arientya Darryl Kurniawati; Shinta Okta Naviska (JOURNAL OF PHARMACEUTICAL (JOP), 2025)
Background: Low medication literacy can increase the risk of medication errors that could potentially compromise safety. This study aims to analyze the influence of sociodemographic factors on medication literacy levels in the Semarang City community based on the Health Belief Model (HBM) theoretical approach. Methods:  This study used an observational, cross-sectional approach. A total of 385 respondents from the Semarang City community who met the inclusion criteria were selected using a purposive sampling technique. Data were collected using a medication literacy questionnaire using the Health Belief Model (HBM) indicator approach, which met validity and reliability tests. Data analysis included univariate and bivariate analyses using the Chi-Square test with a significance level of 0.05. Results: The study showed that the majority of respondents had a high level of medication literacy. The Chi-Square analysis indicated a significant relationship between education level and medication literacy (p < 0.05). Meanwhile, age, gender, and occupation did not show a significant relationship with medication literacy levels (p > 0.05). Conclusion: The results showed that 55.3% of respondents had high medication literacy, 44.2% had low medication literacy, and 0.5% had very low medication literacy. The medication literacy level of the Semarang City community is considered good, with education level being a significant factor (P-value 0.000). Recommendation: The community is encouraged to improve their medication literacy through trusted sources and consultations with pharmacists. Pharmacy personnel play a role in HBM-based drug education. Further research is recommended to use a longitudinal design and include additional research variables